2008
DOI: 10.3201/eid1408.071492
|View full text |Cite
|
Sign up to set email alerts
|

HenipavirusInfection in Fruit Bats (Pteropus giganteus), India

Abstract: We tested 41 bats for antibodies against Nipah and Hendra viruses to determine whether henipaviruses circulate in pteropid fruit bats (Pteropus giganteus) in northern India. Twenty bats were seropositive for Nipah virus, which suggests circulation in this species, thereby extending the known distribution of henipaviruses in Asia westward by >1,000 km.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
116
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(122 citation statements)
references
References 15 publications
5
116
0
1
Order By: Relevance
“…Fruit bats of the genus Pteropus, are the apparent natural reservoir for the virus, and occasionally secrete Nipah virus in their saliva and excrete it in their urine (Young et al, 1996;Yob et al, 2001;Olson et al, 2002;Wacharapluesadee et al, 2005). Studies in Bangladesh, India, and Malaysia also identified neutralizing antibodies against Nipah virus in Pteropus bats (P. vampyrus and P. hypomelanus) (Yob et al, 2001;Epstein et al, 2008;Homaira et al, 2010). P. giganteus, one of the most common fruit bats in Bangladesh, have been found to carry antibodies against Eight Nipah virus outbreaks have been recognized in Bangladesh between 2001(ICDDR,B, 2008Luby et al, 2009).…”
Section: Introductionmentioning
confidence: 94%
“…Fruit bats of the genus Pteropus, are the apparent natural reservoir for the virus, and occasionally secrete Nipah virus in their saliva and excrete it in their urine (Young et al, 1996;Yob et al, 2001;Olson et al, 2002;Wacharapluesadee et al, 2005). Studies in Bangladesh, India, and Malaysia also identified neutralizing antibodies against Nipah virus in Pteropus bats (P. vampyrus and P. hypomelanus) (Yob et al, 2001;Epstein et al, 2008;Homaira et al, 2010). P. giganteus, one of the most common fruit bats in Bangladesh, have been found to carry antibodies against Eight Nipah virus outbreaks have been recognized in Bangladesh between 2001(ICDDR,B, 2008Luby et al, 2009).…”
Section: Introductionmentioning
confidence: 94%
“…Nevertheless, in addition to these countries, the virus has been detected in fruit bats or the bats were seropsitive to NiV antibodies from Cambodia [79], Thailand [90], Indonesia [81], India [23,99], Madagascar in Southern Africa [41] and Ghana in West Africa [22,37]. P. giganteus is the only Pteropus species present in Bangladesh [59].…”
Section: Historical Backgroundmentioning
confidence: 99%
“…An outbreak of acute encephalitis occurred in Siliguri (West Bengal) town of India between January 31 and February 23,2001. A total of 66 probable human cases and 45 deaths were reported.…”
Section: Nipah Virus Infection 399mentioning
confidence: 99%
“…A basic physical examination was conducted, identifying any obvious lesions or abnormalities of the skin, bones, abdomen, thorax, mouth and nervous system. weight (g), and presence of secondary sexual characteristics (Epstein et al 2008).…”
Section: Animal Capture Sample and Data Collectionmentioning
confidence: 99%
“…Post-capture sampling was random. Sex and age-class (estimated by forearm length (mm), weight (g), and presence of secondary sexual characteristics) (Epstein et al 2008) were recorded for each bat.…”
Section: Animal Capture and Samplingmentioning
confidence: 99%